Refraction in adolescents with various severity of Internet addiction and intensity of device use - T.R. Mukhamadeev; R.R. Akhmadeev; E.F. Shaykhutdinova; A.R. Khusniyarova (РМЖ "Клиническая офтальмология")
T.R. Mukhamadeev1, R.R. Akhmadeev2, E.F. Shaykhutdinova3, A.R. Khusniyarova1 1Bashkir State Medical University, Ufa, Russian Federation 2All-Russian Center for Eye and Plastic Surgery of the Bashkir State Medical University, Ufa, Russian Federation 3CJSC "Optimedservis", Ufa, Russian Federation Aim: to assess refraction in adolescent Internet users with various severity of Internet addiction and intensity of device use. Patients and Methods: 84 adolescents (66 girls and 18 boys, mean age 16.0±0.2 years) underwent psychometric and ophthalmic examinations to determine Internet addiction (IA) and duration and experience of using devices and to measure spherical equivalent (SE) (Righton Speedy-K). Results: Internet-addicted adolescents, adolescents with developing IA, and those without IA manifestations accounted for 17.9%, 59.5%, and 22.6%, respectively. The average prevalence of myopia and hypermetropia was 76.2% and 7.1%, respectively. Mean SE was shifted toward myopia (OD -1.5±0.2 D and OS -1.7±0.2). Minimal SE (OD -0.5±0.3 D and OS -0.8±0.3 D) was reported in adolescents with developed IA. SE in adolescents prone to IA was more myopic (OD -1.7±0.3 D and OS -1.9±0.3 D) than in adolescents without signs of IA (OD -1.7±0.4 D and OS -1.6±0.3 D). No significant intergroup differences were reported. No significant correlations between IA severity and refractive errors were revealed by correlation analysis (p=0.729). Meanwhile, a weak negative correlation between refraction and experience using a computer, smartphone, and the Internet (R=-0.11, p=0, 3; R=-0.06, p=0.6; R=-0.13, p=0.24, respectively) was detected. Conclusion: the high prevalence of myopia along with weak correlations between IA and the intensity of device use on the one hand and SE, on the other hand, does not illustrate the lack of a negative impact of information technology on the vision of children and adolescents, but once again establishes the opinion on the complexity of myopia development. Keywords: refraction, myopia, Internet addiction, adolescents, spherical equivalent. For citation: Mukhamadeev T.R., Akhmadeev R.R., Shaykhutdinova E.F., Khusniyarova A.R. Refraction in adolescents with various severity of Internet addiction and intensity of device use. Russian Journal of Clinical Ophthalmology. 2023;23(4):197–201 (in Russ.). DOI: 10.32364/2311-7729-2023-23-4-4.